Single and Multivalued Maps on Parametric Metric Spaces Endowed with an Equivalence Relation. (28th January 2022) - Ali, Muhammad Usman; Aydi, Hassen; Batool, Asma; Parvaneh, Vahid; Saleem, Naeem
Abstract : This article presents the E -parametric metric space, which is a generalized concept of parametric metric space. After that, the discussion is concerned with the existence of fixed points of single and multivalued maps on E -parametric metric spaces satisfying some contractive inequalities defined by an auxiliary function.